Apocynin reduces cytotoxic effects of monosodium glutamate in the brain: A spectroscopic, oxidative load, and machine learning study - BİNGÖL ÖZAKPINAR, ÖZLEM (My University, 2022)
© 2022 Elsevier B.V.Herein, we examined the modulatory effects of Apocynum (APO) on Monosodium Glutamate (MSG)-induced oxidative damage on the brain tissue of rats after long-term consumption of blood serum components by biochemical assays, Fourier transform infrared spectroscopy (FTIR), and machine learning methods. Sprague-Dawley male rats were randomly divided into the Control, Control + APO, MSG, and MSG + APO groups (n = 8 per group). All administrations were made by oral gavage saline, MSG, or APO and they were repeated for 28 days of the experiments. Brain tissue and blood serum samples were collected and analyzed for measurement levels of malondialdehyde (MDA), glutathione (GSH), myeloperoxidase (MPO), superoxide dismutase (SOD) activity, and Spectroscopic analysis. After 29 days, the results were evaluated using machine learning (ML). The levels of MDA and MPO showed changes in the MSG and MSG + APO groups, respectively. Changes in the proteins and lipids were observed in the FTIR spectra of the MSG groups. Additionally, APO in these animals improved the FTIR spectra to be similar to those in the Control group. The accuracy of the FTIR results calculated by ML was 100%. The findings of this study demonstrate that Apocynin treatment protects against MSG-induced oxidative damage by inhibiting reactive oxygen species and upregulating antioxidant capacity, indicating its potential in alleviating the toxic effects of MSG.
Keywords: Fizik; Atom ve Molekül Fiziği; Kimya; Analitik Kimya; Fizikokimya; Spektroskopi; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Atomic and Molecular Physics; Chemistry; Analytical Chemistry; Physical Chemistry; Spectroscopy; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; ALETLER & GÖSTERİM; KİMYA, ANALİTİK; SPEKTROSKOPİ; FİZİK, ATOMİK, MOLEKÜLER VE KİMYASAL; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; CHEMISTRY; PHYSICS; INSTRUMENTS & INSTRUMENTATION; CHEMISTRY, ANALYTICAL; SPECTROSCOPY; PHYSICS, ATOMIC, MOLECULAR & CHEMICAL; Fizik Bilimleri; Atom ve Moleküler Fizik ve Optik; Enstrümantasyon; Physical Sciences; Atomic and Molecular Physics, and Optics; Instrumentation; Monosodium glutamate; Apocynin; Brain tissue; Oxidative load; FTIR; Machine learning; SECONDARY STRUCTURE; HYPERTENSIVE-RATS; AGONISTS; STRESS; DAMAGE; ASSAY; BURST